Skill-Employability Development Models (SEDM) based on Academic Data Mining (ADM) - Jain, Swati; Jain, Vikas Kumar; Kashyap, Sunil Kuamr (International Journal of Computer Sciences and Engineering, 2025)
10 scientific techniques are used to analyze the academic data in this paper. Hence the new factors are obtained to generalize the objective of academics. The illustration is given in this paper for applying this compact method to the academic institutes. New algorithm is proposed to execute the model. These big data have been unutilized mostly. The present study is proposed several model based on modern scientific and computing technique for utilizing these big data. The applicability, usefulness, significance and importance of these big data are studied in this project.